Governance Improvements and Sovereign Financing Costs in Developing Countries - Brown, Michael (World Bank, Washington, DC, 2019)
More and more developing country governments are tapping the global debt capital markets. Thisis increasing the amount of finance available for development, but at a considerably higher costthan traditional external borrowing on concessional terms. Using a novel methodology based onestimating sovereign credit ratings using the Moody's scorecard, and examining the associationsbetween these ratings and the World Bank's Country Policy and Institutional Assessment (CPIA)scores, this paper examines how making improvements in the quality of economic policies andinstitutions can help lower governments' financing costs. Better CPIA scores are associated withbetter estimated ratings and materially lower financing costs; on average, improvements which aresufficient to increase a CPIA indicator score by 1 point are associated with interest costs which are lower by about 170 basis points. Estimated cost savings are the largest for countries with weaker initial ratings and commensurately high external debt issuance costs, consistent with governance concerns contributing significantly to the large risk premia faced by weaker borrowers.